Vir inversus - Männlichkeiten im spanischen Schelmenroman - Schuhen, Gregor (transcript-Verlag, 2018)
Picaresque novels are violent, satirical and usually dominated by males. Gregor Schuhen illuminates this combination from the viewpoint of masculinity studies and explores specifically male practices and ideals
Description based on online resource; title from PDF title page (publisher's Web site, viewed 25. Jul 2018)
Keywords: Allgemeine Literaturwissenschaft; Early Modernity; Frühe Neuzeit; Gender Studies; Gender; General Literature Studies; Geschlecht; Lazarillo de Tormes; Literary Studies; Literatur; Literature; Literaturwissenschaft; Männlichkeitsforschung; Masculinity Studies; Romance Studies; Romanistik; Spain; Spanien; Spanische Literatur; Spanish Literature; Schelmenroman; Männlichkeit -- Motiv; Spanisch; Hochschulschrift